Effectiveness of Cognitive Behavior Therapy Counseling Group Setting in Overcoming Student’s Social Anxiety - Fitriana Fitriana; Firman Firman; Daharnis Daharnis (Fakultas Ilmu Pendidikan UNP)
Social anxiety is one of the important factors that can obstruct students in the process of achieving the development to the optimal direction. Anxiety begins maladaptive cognitive, resulting in ineffective behavior. CBT is one approach to maladaptive cognitive restructuring and ineffective behavior. This study aims to examine the effectiveness of CBT counseling group settings in overcoming students' social anxiety. This research uses a quantitative approach with Quasi Experiment method through The Non Equivalent Control Group design. The subjects were 9 students of control group and 9 students of the experimental group. Data were analyzed using Wilcoxon Signed-Rank Test and Kolmogorov Smirnov 2 Independent Samples. The research findings show that CBT counseling group setting is effective in overcoming student social anxiety. The results of this study can be used as one of the strategies in overcoming the social anxiety of students.